Patterns and Sources of Errors in EFL Descriptive Writing: Evidence from Universitas Jambi Students - Trie Lestari; Nunung Fajaryani; Yulhenli Thabran (Universitas Islam Ogan Komering Ilir Kayuagung, 2026)
This study investigates the types and causes of errors in descriptive writing produced by first-semester EFL students, focusing on texts describing people and places. Data were collected through two writing tasks administered to a purposively selected class, complemented by interviews with six representative students. Using Dulay’s surface strategy taxonomy, errors were classified into omission, addition, misformation, and misordering, while their causes were analyzed based on the frameworks of Brown and Norrish. The findings indicate that omission and misformation were the most frequent error types, reflecting students’ limited mastery of basic grammatical features such as subject-verb agreement, article usage, and adjective order. Interview data supported the written analysis, revealing contributing factors such as inadequate grammatical knowledge, native-language interference, and limited attention to linguistic accuracy. Although the small purposive sample limits generalizability, the study offers pedagogical insights to improve EFL writing instruction by enhancing grammar awareness and self-revision strategies.